(untitled) (NPRC Journal of Multidisciplinary Research, 2024)
This study examines trends in working capital management (WCM) research over the past decade, focusing on key contributors and significant themes. Utilizing data from the Dimensions AI database, we provide an overview of WCM from 2015 to 2024. A systematic review methodology guided our literature gathering, beginning with a keyword search on October 18, 2024, using terms like "working," "capital," "management," and "trend." The final dataset comprised 198 peer-reviewed articles and conference proceedings, ensuring the robustness of our findings. Our analysis reveals fluctuating publication trends, peaking at 35 publications in 2021, followed by a decline in recent years. Key authors, including Pais et al. and Parker et al., emerged as influential figures, with substantial contributions from institutions such as the Ghulam Ishaq Khan Institute and Hamad Bin Khalifa University. The United States and Pakistan lead in research output. Additionally, bibliographic coupling networks highlight clusters focusing on profitability, gaps in empirical research, digitalization in supply chain finance, and practices in family firms. The findings underscore the growing importance of effective WCM in enhancing organizational performance while identifying gaps, particularly in developing economies. Future research should address these gaps to improve both academic discourse and practical applications in the field.